360-Degree Knowledge Management And The Balanced Scorecard - Hariharan, Arun (Journal of Knowledge Management Practice, 2011)
This article explores the relationship between the Balanced Scorecard (BSC) and the 360-degree Knowledge Management (KM) model. It shows how 360-degree KM and the Balanced Scorecard can not merely co-exist but complement each other so a user gets the maximum results from both.